EPIDEMIOLOGICAL STUDY OF MANAGEMENT SYPHILIS IN A MUNICIPALITY OF NORTHWEST FLUMINENSE, RJ - Ferreira Simões, Roberta; Ribeiro Dutra Souza, Josyleide; Maria da Fonseca Souza, Sônia; Capita Quarto, Lucas; Crispim França Luquetti, Eliana (LINKSCIENCEPLACE, 2026)
This article was drawn up from a survey in the database of a Municipal Health Unit, in the northwest of the State of Rio de Janeiro, on the percentage of pregnant women infected with syphilis (STDs) from February to August 2017. Through this, it sought to deepen and discuss several aspects with the purpose of identifying the actions of combat and control of syphilis in pregnant women, as well as the expansion of the access and the improvement of the quality of prenatal care. It was concluded that it is necessary to implement new strategies that can reduce the transmission of syphilis among pregnant women, among them the popularization of the theme in the initiatives of continuing education of professionals, prevention and treatment, guidelines on the regular use of condoms, early diagnosis in women of reproductive age and partners, and performing the diagnostic test on women intending to become pregnant.